Da janela à alcova : a literatura urbana Alencariana e as estratégias amorosas no Rio de Janeiro oitocentista (1856–1875) - Ferreira, Allan Themístocles Galdino (2019)
The urban novels of José de Alencar (1829 - 1877) have clues representing the most varied love tactics used by wealthy young people and adults of the second half of the nineteenth century, in the city of Rio de Janeiro. Such works sound like mouthpieces of this carioca society, presenting elements that make historians able to know about some aspects of flirting, dating, getting engaged and getting married in that period. Cinco Minutos (“Five Minutes”) (1856), A Viuvinha (“The Little Widow”) (1857), Lucíola (1862), A Pata Da Gazela (“The Gazelle's Foot”) (1870) and Senhora (“Madam”) (1875) were novels written by Alencar by which the present study intended to answer the following questions: 1) Which are the love strategies represented in the sources listed? 2) Which moral and / or disciplinary assumptions regarding love and sexuality can be identified? 3) Which economic and social values are present in the works? Thus, based particularly on the assumptions of Roger Chartier, Carlo Ginzburg, Michel Foucault, Iam Watt, Antônio Cândido, Thales de Azevedo, Mary Del Priore, Nizza da Silva, Muriel Nazzari among others, it was possible to perceive a wide range of love tactics undertaken by young people and adults between 1856 and 1875, in an urban society surrounded by capitalist and religious values, which, in the framing and consolidation of bourgeois groups, led to the rise of the court novels. Such works which, while bringing readers closer to the reality around them, educated them, disciplined them concerning love, affection and sexuality, progressively following the modernizing tonic of the civilizing agenda undertaken by Emperor Dom Pedro II.